Racemisation in Chemistry and Biology. Issue 17 (20th January 2020) - Ballard, Andrew; Narduolo, Stefania; Ahmed, Hiwa O.; Keymer, Nathaniel I.; Asaad, Nabil; Cosgrove, David A.; Buurma, Niklaas J.; Leach, Andrew G.
Abstract: The two enantiomers of a compound often have profoundly different biological properties and thus their liability to racemisation in aqueous solutions is an important piece of information. The authors reviewed the available data concerning the process of racemisation in vivo, in the presence of biological molecules (e.g., racemase enzymes, serum albumin, cofactors and derivatives) and under purely chemical but aqueous conditions (acid, base and other aqueous systems). Mechanistic studies are described critically in light of reported kinetic data. The types of experimental measurement that can be used to effectively determine rate constants of racemisation in various conditions are discussed and the data they provide is summarised. The proposed origins of enzymatic racemisation are presented and suggest ways to promote the process that are different from processes taking place in bulk water. Experimental and computational studies that provide understanding and quantitative predictions of racemisation risk are also presented. Abstract : Shedding light on racemisation : Although the importance of racemisation is well known, the process remains poorly studied. In this Review, the available data concerning chemical (acid and base) and enzymatic catalysis of racemisation and predictive tools are presented and discussed. The paucity of relevant data is striking.